CD44 loss of function sensitizes AML cells to the BCL-2 inhibitor venetoclax by decreasing CXCL12-driven survival cues - Yu, Xiaobing; Munoz-Sagredo, Leonel; Streule, Karolin; Muschong, Patricia; Bayer, Elisabeth; Walter, Romina J.; Gutjahr, Julia C.; Greil, Richard; Concha, Miguel L.; Müller-Tidow, Carsten; Hartmann, Tanja N.; Orian-Rousseau, Véronique (Blood, 2021)
Acute myeloid leukemia (AML) has a poor prognosis under the current standard of care. In recent years, venetoclax, a BCL-2 inhibitor, was approved to treat patients who are ineligible for intensive induction chemotherapy. However, complete remission rates with venetoclax-based therapies are hampered by minimal residual disease (MRD) in a proportion of patients, leading to relapse. MRD is a result of leukemic stem cells being retained in bone marrow protective environments; activation of the CXCL12-CXCR4 pathway was shown to be relevant to this process. An important role is also played by cell adhesion molecules such as CD44, which has been shown to be crucial for the development of AML. Here we show that CD44 is involved in CXCL12 promotion of resistance to venetoclax-induced apoptosis in human AML cell lines and AML patient samples, which could be abrogated by CD44 knock down, knockout, or blocking with an anti-CD44 antibody. Split-Venus bimolecular fluorescence complementation showed that CD44 and CXCR4 physically associate at the cell membrane upon CXCL12 induction. In the venetoclax-resistant OCI-AML3 cell line, CXCL12 promoted an increase in the proportion of cells expressing high levels of embryonic stem cell core transcription factors (ESC-TFs: Sox2, Oct4, Nanog) abrogated by CD44 knockdown. This ESC-TF-expressing subpopulation which could be selected by venetoclax treatment, exhibited a basally enhanced resistance to apoptosis and expressed higher levels of CD44. Finally, we developed a novel AML xenograft model in zebrafish, which showed that CD44 knockout sensitizes OCI-AML3 cells to venetoclax treatment in vivo. Our study shows that CD44 is a potential molecular target for sensitizing AML cells to venetoclax-based therapies.